ANALISIS KESIAPAN KESATUAN PENGELOLAAN HUTAN YOGYAKARTA SEBAGAI BADAN LAYANAN UMUM DAERAH - Sulistya Ekawati,M.Sc; Fentie Julianti Salaka; Kushartati Budiningsih (Jurnal Analisis Kebijakan Kehutanan, 2018)
The institution of Yogyakarta Forest Management Unit (FMU) is considered still bureaucratic which makes it difficult to respond quickly to problems related with financial management. Although Sub-National Public Service Agencies (SNPSA)  is an independent financial management institution, but Yogyakarta FMU is not confident yet to perform this scheme. This study aims to analyze some legislation related with independent financial management, formulate supporting legal instruments and provide institutional options for independent financial management that would be matched for Yogyakarta FMU. By using a qualitative analyse approach with a paradigm of critical legal theory the study showed that there was similiarity regarding principles of effeciency and effectiveness in forest and financial management carried out by FMU and SNPSA . However, in order to be independent, FMU needs to be self-sufficient through synchronization and revision of several regulations related with it. It is suggested that hybrid public organization as an independent financial management for FMU to gain political support from local governments, strong leadership, preparation of capable human resources and improvement on accounting management.